Celebrating Birthdays for Maril Turpin, Shirley Griffenhagen and Leslie Prusia at the Watkins' Home - Watkins, Howard::::::::: (1986)
Leslie Prusia, Christine Watkins, Maril Turpin, Peggy Sanders and Shirley Griffenhagen seated at dining table